Financing market-oriented dairy development. The case of Ada'a - Liben Woreda Dairy Association, Ethiopia - Tegegne, Azage (2003)
The dairy industry needs to be optimised through organising milk production, processing, preservation and marketing in a well-coordinated way. With the recent changes in government policies featured by liberalisation and encouragement of the private sector to participate in the development of almost all aspects of the national economy, there exist immense opportunities to develop and improve the agricultural sub-sector. With the increasing demand for diverse and quality animal products, prices are bound to escalate unless production increases proportionally. Bridging the wide demand supply gap calls of the designing of appropriate and sustainable dairy development strategies based on the specific agro-ecology and felt needs smallholder farmers. Currently, a number of smallholder and commercial dairy farms are emerging mainly in urban and peri-urban areas. Smallholder rural dairy farms are also increasing in number in areas where there is market access. However the transaction cost of milk marketing is a major problem for individual smallholder farmers. The natural evolution resulting from such problems is the formation of milk units and dairy marketing associations where farmers can collect, process and market milk and milk products. One of the pioneer associations recently established in Debre Zeit town is the Ada'a Liben Woreda Dairy and Dairy Products Marketing. Association. This paper discusses milk marketing and its problems for these smallholder farmers; livestock and its linkage to the social and cultural lives; current status, financing and future plans. It also illustrates milk collection centres; achievements of the association; cooperative members; and the annual capital shares, profit and loss of the association.